NPL contributions to the standardisation and validation of contemporary medical thermometry methods. (3rd June 2019) - Machin, G; Simpson, R; McEvoy, H C; Whittam, A
Abstract: Since the advent of reliable mercury-in-glass thermometers in the latter part of the 19th century the practice of clinical thermometry was thought to be a solved issue. However with advances in technology there has, in recent decades, been a proliferation of temperature measurement methods applied to medical science. Many of these have been introduced because of the clinical benefit they confer, nevertheless, in some cases the metrological foundation and infrastructure to ensure sound measurement was not in place. This paper will focus on the standardisation activity undertaken by the UK's National Physical Laboratory (NPL) to support reliable temperature measurement, using a number of innovative methods, in a clinical setting.